A comparison of self-report versus objectively measured physical activity in African-origin adults and the role of adiposity: a prospective cohort study - Davies, Jessica (Department of Public Health and Family Medicine, 2026)
Understanding physical activity (PA) patterns, including the domain, duration, and intensity, among different populations where the prevalence of obesity varies may provide insight into the role of PA in obesity prevention. This thesis consists of two parts; Part A includes the rationale, aims and objectives of the current study, and the methodology, data analysis plan and ethical considerations. Part B consists of a manuscript which outlines and discusses the findings of the study. The study presented in this thesis is a secondary data analysis from the Modeling the Epidemiologic Transition Study (METS)-Microbiome. Approximately 2,000 men and women of predominantly African-origin, between the ages of 35 and 55, were recruited and enrolled in the METS-Microbiome study between January 2017 and December 2019. Participants were previously enrolled in a prospective study of weight change (METS) and included 5 countries spanning the epidemiologic transition; rural Ghana; peri-urban South Africa; urban Jamaica; the Seychelles; and suburban Chicago, USA. PA was measured using objective PA monitoring and the self-report Global PA Questionnaire (GPAQ). Adiposity was measured using bioelectrical impendence analysis (BIA), which calculates fat and fat free mass. A basic health history was obtained from the participants, including the health history and socio-demographic information. Using objectively measured PA, it was found after adjusting for site and sex, that Ghanaians do 76 min/day more PA compared to those in the US (95% CI: 42.51, 108.67, p<0.05). Similarly, females perform 64 min/day less PA than males (95% CI: -88.44, -39.84, p<0.05). Overweight/obese people do 31 min/day less PA than normal weight people adjusting for sex (95% CI: -55.48, -6.69, p=0.01). Finally, females perform 54 min/day less PA than males (95% CI: -78.57, -29.32, p<0.05).